Ionic liquids modified dummy molecularly imprinted microspheres as solid phase extraction materials for the determination of clenbuterol and clorprenaline in urine - Yan, Hongyuan; Liu, Suting; Gao, Mengmeng; Sun, Ning (Journal of Chromatography A, 2013)
•Ionic liquid modified dummy imprinted microspheres (DMIMs) were synthesized.•DMIMs-SPE for rapid isolation of clenbuterol and clorprenaline in urine.•Matrix interferences were removed and analytes were concentrated.•Problem of template leakage on quantitative analysis was eliminated. New ionic liquid modified dummy molecularly imprinted microspheres (DMIMs) were synthesized by aqueous suspension polymerization using phenylephrine as dummy template and 1-allyl-3-ethylimidazolium bromide as co-functional monomer. The obtained DMIMs were characterized by Fourier transform infrared (FT-IR) and scanning electron microscopy (SEM), and empolyed as the special sorbent of solid-phase extraction for isolation of clenbuterol (CLB) and clorprenaline (CLP) from urine sample. The results indicated that the ionic liquid modified polymers were monodispersed microspheres and had high selectivity and adsorbability to CLB and CLP, and the matrix interferences could be efficiently eliminated from the samples. Meanwhile, the effect of template leakage of DMIMs on quantitative analysis was avoided. Compared with other commercial sorbents (HLB, PCX, C18 and SCX), the DMIMs exhibited higher affinity and purification ability to CLP and CLB. Under the optimized conditions, good linearity was observed in a range of 0.90–400μgL−1 (r2=0.9999) with LOD of 0.19 and 0.070μgL−1 for CLP and CLB, respectively. The recoveries at three spiked levels were ranged from 93.3% to 106% with RSD≤5.6% (n=3).